Pengaruh Kemudahan, Kecepatan dan Keamanan Penggunaan Qris Pada UMKM Halal Kota Medan - Nasution, Arfiany Sepyanty Putri; Harahap, Isnaini; Aslami, Nuri (Gorontalo State University, 2025)
The implementation of the Indonesian Quick Response Code or Qris Standard is the latest development in buying and selling transactions for MSME players. Small, medium, and micro enterprises in Medan City in various industries have grown rapidly. The purpose of this study is to determine the ease, speed, and security of halal MSMEs in Medan City who choose to use Qris by using the assumptions of the technology acceptance model. This research uses quantitative methods and quantitative descriptive methods. The results of this study indicate that convenience and security have a significant effect on halal MSMEs in Medan City that use QRIS, while speed has no significant effect on halal MSMEs in Medan City that use QRIS. The research conclusion regarding the impact of ease, speed, and security of using QRIS among halal MSMEs in Medan City shows that these three factors play an important role in increasing the acceptance and use of QRIS among MSME participants. The ease of use of QRIS has an impact on the ease of transactions, the speed of the payment process, and security that provides a sense of security for businesses and consumers. Overall, the application of QRIS can encourage the development of halal MSMEs in Medan City by increasing transaction efficiency and convenience.